Junior High School Teachers’ Awareness of Foreign Language Anxiety in English Classroom - Fadila, Anwar; Rachma, Nita Sitta; Mar'an, Desy Awal; Nurzafira, Istiqomah; Maulita, Rizki (English Language Education Study Program, 2024)
Foreign language anxiety (FLA) has been a significant area of research in second language acquisition, due to its impact on language learning. However, research focusing on teachers’ awareness of students' FLA remains limited, despite suggestions in the literature that educators play a crucial role in helping students cope with anxiety. To address this gap, the present study explores the awareness of junior high school teachers on students’ FLA. A case study approach was employed, utilizing semi-structured interviews with three junior high school English teachers in Lampung, Indonesia. The data were analysed thematically. The findings indicate that the teachers were generally aware of FLA and could identify its signs, causes, and impact on language learning. However, they appeared to lack awareness that FLA is context-specific and distinct from other forms of anxiety. The study concludes with implications for teacher training and pedagogical practice in relation to managing FLA in the classroom.